Analysis Of Usability In FIFA 15 and Pro Evolution Soccer (PES) 15 Using Mc Call’s Quality Factors - Yudistira Yudistira; Ahmad Subhan Yazid; Agung Fatwanto (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2016)
FIFA 15 and Pro Evolution Soccer (PES) 15 are soccer games that are popular in Indonesia. Usability testing needs to be done to assess user interest and satisfaction with both and provide an overview of the comparison of them. The framework used for testing is McCall’S. The test combines operability matrix and training matrix to determine software quality. McCall’S was chosen because it has a reliable and comprehensive quality factor indicators. The results of the tests carried out were data on the operability level of PES15 games of 76.81% ± 15.76% and FIFA15 games of 70.65% ± 20.73%. Testing of training matrices produced 15.96 ± 21.74 seconds for PES15 and 78.29 ± 25.73 seconds for FIFA15 game training matrix. The data shows that reusability of PES15 is better than FIFA15.